Efficacy and tolerability of desensitization in the treatment of delayed drug hypersensitivities to anti-tuberculosis medications. (February 2019) - Ban, Ga-Young; Jeong, Yoon-Jeong; Lee, So-Hee; Shin, Seung-Soo; Shin, Yoo-Seob; Park, Hae-Sim; Kim, Seung-Hyun; Ye, Young-Min
Abstract: Background: Delayed drug hypersensitivity to first-line anti-tuberculosis medication is a major challenge in tuberculosis treatment. Objective: This study was performed to investigate the efficacy/tolerability of desensitization therapy in treatment of first-line anti-tuberculosis medication hypersensitivity and the usefulness of immunologic evaluation therein. Methods: This study was conducted as a prospective, observational cohort study. Subjects who experienced hypersensitivity reactions, including maculopapular exanthema (MPE) and drug reaction with eosinophilia and systemic symptoms (DRESS), to first-line anti-tuberculosis medications (isoniazid [INH], ethambutol [EMB], rifampin [RFP], and pyrazinamide [PZA]) were enrolled. Patch, intradermal, lymphocyte transformation, and oral provocation tests were performed to determine culprit drugs, which were desensitized with rapid and graded challenge protocols. Breakthrough reactions (BTRs) during or after desensitization were assessed. Results: In total, 31 desensitization treatments (INH, 8; EMB, 8; RFP, 11; PZA, 4) to 12 patients (8 with MPE and 4 with DRESS) were performed. The overall success rate of desensitization was 80.7%. All the study subjects except one completed the full course of anti-tuberculosis treatment. The overall BTR free rate was 64.5%. Sixteen (80%) treatments for MPE and four (36.4%) for DRESS were BTR free ( P  = 0.023). Drugs that were positive on any two of three immunologic studies showed significantly high BTR rates ( P  = 0.014), although this was not correlated with desensitization failure rate. Conclusion: Rapid desensitization therapy to multiple anti-tuberculosis medications for delayed drug hypersensitivity was safe and successful. Combination of multiple immunologic evaluations may predict BTR although it needs validation in larger studies. Highlights: The overall success rate of desensitization to anti-tuberculosis medications was 80.7% in the present study. The breakthrough reaction free rate of desensitization to anti-tuberculosis medications was 64.5%. Combination of multiple immunologic evaluations may predict the occurrence of breakthrough reaction.